Tumor-derived exosomes: the next generation of promising cell-free vaccines in cancer immunotherapy - Naseri, Marzieh; Bozorgmehr, Mahmood; Zöller, Margot; Ranaei Pirmardan, Ehsan; Madjd, Zahra (OncoImmunology, 2020)
Identification of immunogenic tumor antigens that are efficiently processed and delivered by dendritic cells to prime the immune system and to induce an appropriate immune response is a research hotspot in the field of cancer vaccine development. High biosafety is an additional demand. Tumor-derived exosomes (TEXs) are nanosized lipid bilayer encapsulated vesicles that shuttle bioactive information to the tumor microenvironment facilitating tumor progression. However, accumulating evidence points toward the capacity of TEXs to efficiently stimulate immune responses against tumors provided they are appropriately administered. After briefly describing the function of exosomes in cancer biology and their communication with immune cells, we summarize in this reviewin vitroand preclinical studies eliciting the potency of TEXs in inducing effective anti-tumor responses and recently modified strategies further improving TEX-vaccination efficacy. We interpret the available data as TEXs becoming a lead in cancer vaccination based on tumor antigen-selective high immunogenicity.
Gesehen am 24.08.2020